an-Naqd ‘ala Tarjamati Kitab ‘Izah an-Nasyiin li Mustafa al-Ghulayaini - Hanun Khiyarotun Nisa’ (Jurnal Internasional Pendidikan Bahasa Arab, 2019)
The Book of ‘Izah an-Nasyiin is a collection of writings written by one of the great Egyptian scholars, Mustafa al Ghulayaini, in the newspaper "al-Mufid". This book contains a variety of moral issues, social, nationalism, leadership, and education. This book is very well received and has a great influence on the hearts of readers. This book translated into Indonesian by M. Fadlil Said an-Nadwi. In reality, this translated book requires criticism. It must be known that criticism is not only limited to the search for deficiencies or mistakes but also gives high appreciation to translators, editors and, publishers. The purpose of this study is to describe grammatical problems in the translation work along with its solutive efforts. This translation critique research rests on Newmark translation theory, which is focus on the original language and focus on the transfer language. This is because the book of ‘Izah an-Nasyiin is more representative of the author's thoughts in ethics or morals delivered with literary expressions. In many cases, the researcher finds translation models that tend to be closer to the text and in other cases closer to the reader. The researcher focused on evaluating the work of translation in grammatical problems and solutive efforts. The results of this study are that the researcher found translation evaluations on three grammatical problems; tarkib isnadi or jumlah, tarkib bayani and tarkib idafi.